PERBANDINGAN HASIL BELAJAR MELALUI GI DAN SFAE DENGAN MEMPERHATIKAN KEMAMPUAN AWAL SISWA - Ali Yanto; R. Gunawan Sudarmanto; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2014)
This study aims to determine : 1) differences in learning outcomes and the use of GI, SFAE. 2) differences in the results of the study of high -ability students early, medium, and low. 3) differences in learning outcomes and the learning and ability early students. 4) the interaction between the of GI, SFAE between students who have knowledge on the learning outcomes of the. 5) differences in the effectiveness of the of GI, SFAE. This study used an experimental method with a comparative approach. Means of collecting data in the form 53 students. The results showed : 1) there was no difference in the results of the study with students using GI, SFAE. 2) there are differences in learning outcomes between students who have the ability of early. 3) there are differences in learning outcomes and economic l ability early students using GI, SFAE. 4) there is no interaction between the of GI with SFAE and between students who have knowledge of on the learning outcomes of the.5) no difference in effectiveness between the GI, SFAE.                                                 Penelitian bertujuan mengetahui: 1) perbedaan hasil belajar menggunakan GI, SFAE.2) perbedaan hasil belajar siswa berkemampuan awal tinggi, sedang, dan rendah. 3) perbedaan hasil belajar antarmodel pembelajaran dan antarkemampuan awal siswa. 4) interaksi antara GI, SFAE siswa yang memiliki kemampuan awal tinggi, sedang dan rendah terhadap hasil belajar. 5) perbedaan efektivitas GI, SFAE. Metode eksperimen pendekatan komparatif. Pengumpul data tes 53 siswa.Hasil penelitian:1) tidak ada perbedaan hasil belajar siswa menggunakan GI dengan SFAE. 2)ada perbedaan hasil belajar antara siswa yang memiliki kemampuan awal. 3)ada perbedaan  hasil belajar antarmodel dan antarkemampuan awal siswa menggunakan GI, SFAE. (4) tidak ada interaksi antara GI dengan SFAE dan siswa yang memiliki kemampuan awal terhadap hasil belajar. (5)ada perbedaan efektivitas antara GI dengan SFAE. Kata kunci: gi,hasil belajar,kemampuan awal, sfae